Barrett's Oesophagus Surveillance versus endoscopy at need Study (BOSS): protocol and analysis plan for a multicentre randomized controlled trial. (September 2015) - Old, Oliver; Moayyedi, Paul; Love, Sharon; Roberts, Corran; Hapeshi, Julie; Foy, Chris; Stokes, Clive; Briggs, Andrew; Jankowski, Janusz; Barr, Hugh; ,
Objectives: The absolute annual risk of patients with Barrett's oesophagus (BO) developing oesophageal adenocarcinoma (OAC) is ≤0.5%. Screening BO patients for malignant progression using endoscopic surveillance is widely practised. To assess the efficacy and cost-effectiveness of this, we developed a protocol for a randomized controlled trial of surveillance versus 'at need' endoscopy. Methods: In a multicentre trial, 3400 BO patients randomized to either 2-yearly endoscopic surveillance or 'at need' endoscopy will be followed up for 10 years. Urgent endoscopy will be offered to all patients who develop symptoms of dysphagia, unexplained weight loss >7lb (3.2kg), iron deficiency anaemia, recurrent vomiting, or worsening upper gastrointestinal symptoms. Participants must have endoscopically and histologically confirmed BO, with circumferential BO ≥1cm or maximal tongue/island length ≥2 cm. Candidates with existing oesophageal high-grade dysplasia or cancer, or previous upper gastrointestinal cancer will be excluded. Primary outcome will be overall survival. Secondary outcomes will be cost effectiveness (cost per life year saved and quality adjusted life years); cancer-specific survival; time to OAC diagnosis and stage at diagnosis; morbidity and mortality related to any interventions; and frequency of endoscopy. Conclusions: This randomized trial will provide data to evaluate the efficacy and cost-effectiveness of screening BO patients for OAC.